Single lives : modern women in literature, culture, and film - Fama, Katherine; Lagerwey, Jorie; Williams, Andreá N.; Clark, Jennifer S.; DeWolfe, Elizabeth; Wojcik, Pamela Robertson; Mastandrea, Martina; Celello, Kristin; Kania, Ursula; Liggins, Emma (Rutgers University Press, 2022)
"Single Lives is a collection of singleness studies essays from the interdisciplinary humanities that explores the last two hundred years of literature and popular media by, about, and for single women in the US and the UK. Independent women have always been a center around which social anxieties and excitement coalesced. Moving between the family home and domestic independence, between household and public labor, and between celibacy and a range of sexual relations, the single woman remains a literary and cultural focus, as she has been from the 19th to the 21st centuries. This collection offers readers the opportunity to uncover the social, political, economic, and cultural connections between the "singly blessed" women and "bachelor girls" of the 19th and early 20th century and "all the single ladies" of the 21st century. Essays read singleness across genre and field, offering new approaches to studying modern and contemporary single women in literature, film, and history. Authors engage scholarship from wide ranging fields of social history, women's studies, queer theory, and Black feminism. The collection reads familiar texts against the grain, rethinking archival resources, revisiting familiar figures, and exploring new sources: cookbooks, ephemera, personal documents, recovered film histories, and forms of domestic space and labor. This is a book for scholars of gender and sexuality, social history, feminist film and media scholars, and literary historians, and reflects the urgent contemporary interest in single women as a political, economic, and cultural force"--